Patterns of sedentary behavior in adults: A cross-sectional study - Silva, Gustavo O.; Cunha, Paolo M.; Oliveira, Max D.; Christofaro, Diego G. D.; Tebar, William R.; Gerage, Aline M.; Kanegusuku, Hélcio; Correia, Marilia A.; Ritti-Dias, Raphael M. (Frontiers in Cardiovascular Medicine, 2023)
The aim of the current study was to describe the different patterns of sedentary behavior (SB) of adults, their relationships, and associated factors. The sample included 184 adults aged ranging from 18 to 59 years old. SB was objectively measured by an accelerometer and the following SB pattern parameters were obtained: total time in sedentary bouts, mean time of sedentary bouts, and total time in sedentary breaks. Demographic data (age and sex), anthropometry (weight, height, body mass index [BMI]), blood pressure (BP), medical history (self-reported comorbid conditions), and cardiac autonomic modulation, were assessed to identify factors associated with SB. Multiple linear regressions were used to analyze the relationship between SB parameters and the associated factors. The parameters of SB indicated 2.4 (0.9) hours/day for total time in sedentary bouts, 36.4 (7.9) min for the mean time of sedentary bouts, and 9.1 (1.9) hours/day for the total time in sedentary breaks. Multiple adjusted regression indicated that age was the only factor associated with SB patterns (P<0.05) after adjustment for confounding variables (sex, age, BMI, dyslipidemia, systolic and diastolic BP). Young adults [18-39 years old] spent more time in sedentary bouts and less time in uninterrupted sedentary bouts compared to middle-aged adults [40-59 years old] (2.58 (0.88) hours/day vs. 2.13 (0.90) hours/day, respectively; p=0.001 and 34.5 (5.8) min 18-39 y.o. vs. 38.8 (9.6) min 40-59 y.o.; p=<0.001; respectively). The total time in sedentary breaks was similar between age groups (p=0.465). The total time in sedentary bouts was significantly correlated with the mean time of sedentary bouts (r=-0.58; p=<0.001), and with the total time in sedentary breaks (r=-0.20; p=0.006). The mean time of sedentary bouts was significantly related to the total time in sedentary breaks (r=0.19; p=0.007). In conclusion, age seems to be a relevant factor associated with sedentary behavior with young adults spending more time in SB and accumulating this behavior in a higher amount of sedentary bouts compared to middle-aged adults.